Experimental study on the milling process of microchannel - Yanxiao XU; Qingfu QIU; Wei ZHOU (Journal of Hebei University of Science and Technology, 2016)
In order to improve the milling efficiency of microchannels, the micro milling cutter is proposed to fabricate the microchannel array structures on the aluminum alloy sheet. The processing parameters such as back engagement, feed speed and spindle speed are varied to study their influence on the geometry size of microchannels. The result shows that when using the milling cutter with diameter of 0.4 mm, the width of microchannels increases with the increasing of back engagement and feed speed, especially for the back engagement. When the cutting speed is in the range of 6 000~21 000 r/min, the width size of microchannels barely changes with the increasing of spindle speed. So microchannel array structures can be fabricated through selecting optimized processing parameters.